Side-chain quinine-based polymer, preparation method and application of side-chain quinine-based polymer in preparation of anion exchange membrane

By designing the molecular chain structure of quinine polymers, the side chain quinine polymers are synthesized, and the stability and performance problems of the existing quinine anion exchange membrane are solved, and the preparation of high-performance anion exchange membrane is realized. It is suitable for applications such as hydro electrolysis, hydrogen production, fuel cells, etc.

CN119875080AActive Publication Date: 2025-04-25DALIAN UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510029287.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-25
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The existing quinine anion exchange membrane has problems such as chemical stability, ion transport performance and mechanical stability, and it is difficult to meet the requirements of commercial application.

Method used

By designing the structural structure of the quinine polymer molecular chain, side-chain quinine polymers are synthesized, and a specific preparation method is used to form an anion exchange membrane with excellent alkali resistance and high-speed ion transport performance.

Benefits of technology

The chemical stability, ion transport performance and mechanical stability of the anion exchange membrane have been greatly improved. The ion conductivity of 80℃ is greater than 150mS cm-1, and the alkali resistance is excellent. It can meet the application requirements of hydroelectric hydrogen production, fuel cells and energy storage batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875080A_ABST
    Figure CN119875080A_ABST
Patent Text Reader

Abstract

The invention provides a side-chain quinine-based polymer, a preparation method and application of the side-chain quinine-based polymer in preparation of an anion exchange membrane, and belongs to the technical field of fuel cells and hydrogen production by electrolysis of water. The preparation method comprises the following steps: firstly, synthesizing a quinine-based polymer with good alkali resistance from an aromatic monomer, a functional monomer and a quinine monomer through a super-acid catalytic condensation reaction, and secondly, preparing a side-chain quinine-based polymer based on the synthesized quinine-based polymer; and finally, carrying out film casting by taking the side-chain quinine polymer as a main chain polymer, and obtaining the high-performance all-carbon-chain anion exchange membrane in a modification mode of grafting a side chain. The alkaline anion exchange membrane prepared by the invention has excellent chemical stability, ionic conductivity, mechanical property and comprehensive performance, and can be applied to the fields of alkaline fuel cells, water electrolysis, energy storage cells, carbon dioxide conversion, electrodialysis and other electrochemical devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fuel cells and hydrogen production by electrolysis of water, and relates to a side chain type quinine-based polymer, a preparation method and application thereof in preparing anion exchange membranes. Technical Background

[0002] At present, excessive reliance on and exploitation of fossil energy have led to a series of problems such as environmental pollution, energy shortages and greenhouse effects. The world urgently needs to develop green, clean and renewable hydrogen energy to replace fossil fuels. Among them, water electrolysis and fuel cell technology as hydrogen energy conversion technologies have great development prospects. Anion exchange membrane, as one of the key components of water electrolysis and fuel cell technology, can separate the anode and cathode, transport ions, carry catalysts, and prevent fuel leakage, playing an important role in the long-term stable operation of water electrolysis and fuel cells. However, in order to meet practical commercial applications, anion exchange membranes still have shortcomings such as poor stability and low conductivity. Focusing on such key scientific issues, researchers continue to carry out a lot of scientific research exploration to improve their conductivity and long-term stability under alkaline conditions.

[0003] First, different polymer backbones have been studied, including polyarylether, polynorbornene, polybenzimidazole and ether-free aromatic polymers. Among them, ether-containing polymers are easily degraded by the pronuclear erosion of hydroxides, resulting in poor durability and dimensional stability; in contrast, all-carbon polymer backbones are gradually replacing ether-containing polymers due to their good alkali resistance, chemical stability and mechanical strength. Secondly, people have introduced a variety of ion transport groups into the polymer backbone or side chain to improve the ion transport performance and alkali stability of anion exchange membranes. Among them, quinine exhibits excellent alkali stability in the form of a rigid bicyclic cation that is approximately spherical, has low ring strain and constrained conformation, and is not prone to degradation reactions in high-concentration alkali solutions. Therefore, quinine-based polymers, as a new type of anion exchange membrane material, have excellent alkali resistance. However, to date, the ion transport performance of quinine-based anion exchange membranes has not been fully explored and is difficult to meet the requirements of commercial applications. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention aims to provide a method for preparing a side chain quininyl polymer and an anion exchange membrane thereof by structural design of the quininyl polymer molecular chain, so as to solve the problems of chemical stability, ion transport performance and mechanical stability existing in the existing quininyl anion exchange membrane.

[0005] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0006] A side chain quinicin-based polymer, the side chain quinicin-based polymer comprising a quinuclidine structural unit, an aromatic structural unit Ar1, a functional structural unit R1, and a side chain structure R3, the side chain quinicin-based polymer having a structure as shown in the following formula (P) or formula (Q):

[0007]

[0008] Wherein, x is the molar proportion of the side chain structural unit in the polymer chain, %; y is the molar proportion of the functional structural unit in the polymer chain, %; z is the molar proportion of the quinuclidine structural unit in the polymer chain, %; in formula P, x is 10%-50%, z is 50%-90%; in formula Q, x is 10%-50%, y is 0%-40%, and z is 25%-90%.

[0009] Preferably, the structure of R1 is at least one of the following,

[0010]

[0011] Wherein, R2 in the R1 structure is hydrogen or a C1-C10 alkyl group.

[0012] Preferably, the Ar1 structure is at least one of the following aromatic structural monomers:

[0013]

[0014] Wherein, R2 in the Ar1 structure is hydrogen or C1-C 10 of alkyl.

[0015] Preferably, the R3 comprises at least one of the following structures:

[0016]

[0017] Wherein, R2 in the R3 structure is hydrogen or a C1-C10 alkyl group.

[0018] A method for preparing a side chain quininyl polymer comprises the following steps:

[0019] The first step is to synthesize quinine-based polymers;

[0020] Ar1 is dissolved in dichloromethane, and after dissolution, 3-quininone or a mixture of 3-quininone and R1 is added, trifluoromethanesulfonic acid is added dropwise, and the reaction is stirred at a certain temperature. When the reaction liquid becomes very viscous and climbs the pole, the reaction is terminated, and the reaction liquid is poured into deionized water for precipitation, washing, filtering, and drying to obtain a quininyl polymer;

[0021] The reaction temperature is 20-30°C and the reaction time is 4-24h;

[0022] The molar concentration of the monomer in dichloromethane is 1.0-2.0 mol / L;

[0023] When Ar1 is added to 3-quininone, the molar ratio of Ar1 to 3-quininone is 1:(1-1.5); when Ar1 is added to a mixture of 3-quininone and R1, the molar ratio of Ar1, 3-quininone, and R1 is 1:(1-1.5):(0.01-0.5);

[0024] The molar ratio of 3-quinindone to trifluoromethanesulfonic acid is 1:4-9;

[0025] The drying temperature is 80° C. and the drying time is 24 hours.

[0026] The second step is to prepare a side chain quinine polymer;

[0027] The quinine polymer prepared in the first step is dissolved in solvent X, and then potassium carbonate, bromide R3, and methyl iodide are added to the mixture, and the mixture is reacted for a period of time at a certain temperature and away from light. After the reaction, the mixed solution is precipitated in precipitant A, purified and dried to obtain the target solid.

[0028] The reaction temperature is 20-80°C and the reaction time is 12-48h;

[0029] The molar ratio of the quinine polymer: bromide R3: iodomethane: potassium carbonate is 1: (0.1-0.5): 1.5: 2;

[0030] The mass concentration of the quinine-based polymer in solvent X is 0.01 to 0.05 g / mL;

[0031] The solvent X is one or a mixture of two or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone;

[0032] The precipitant A is one or a mixture of two or more of ether, methanol, ethanol, ethyl acetate, acetone, and water;

[0033] The drying temperature is 80° C. and the reaction time is 24 h.

[0034] An application of a side chain quinine-based polymer for preparing a side chain quinine-based polymer anion exchange membrane, wherein the OH - The anion exchange membrane has the structure shown in the following formula (S) and (T):

[0035]

[0036] The preparation method comprises the following steps:

[0037] Further, the dried side chain quinine polymer is dissolved in solvent Y to prepare a membrane solution, filtered, degassed, and the solution is poured onto a clean plate and dried to obtain an anion exchange membrane; the anion exchange membrane is immersed in a KOH solution at room temperature, and after sufficient ion exchange, it is washed with deionized water until neutral, and dried to obtain OH. - The polymer anion exchange membrane is a side chain quinine-based polymer anion exchange membrane having good ion transport performance, alkali resistance stability and dimensional stability.

[0038] The membrane solution concentration is 3-10wt%;

[0039] The drying temperature is 60-80°C and the time is 6-24 hours;

[0040] The soaking time is 24-48 hours, and the concentration of the KOH solution is 1-2 mol / L.

[0041] The solvent Y is one or a mixture of two or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

[0042] The present invention has the following beneficial effects:

[0043] (1) The innovation of the present invention is: synthesizing an ether-free polymer skeleton and a strong alkali-resistant cationic group to improve the intrinsic alkali resistance of AEMs; based on the essence of microphase separation morphology construction, combined with the strategy of remote grafting, using the cation-dipole driving force, inducing the directional aggregation of hydrophilic ion domains to construct a high-speed ion transmission water channel, improving the ion conductivity while maintaining dimensional stability, and using large-volume aromatic hydrophobic structural units to introduce more free volume into the membrane, breaking the tight stacking and interlocking between linear molecular chains, providing convenience for the movement of the skeleton and cationic groups, while increasing the molecular weight of the polymer and increasing the steric hindrance, reducing the OH group - Risk of attack.

[0044] (2) The present invention can prepare a side chain quinine polymer anion exchange membrane by designing quinine polymer molecules, which has good mechanical strength and ion transport performance, and the ion conductivity at 80°C is greater than 150 mS cm -1 , excellent alkali resistance and stability, at 2 mol L -1 After being immersed in KOH solution for 10,000 hours, its ionic conductivity does not decay, which can meet the application requirements of water electrolysis for hydrogen production, fuel cells and energy storage batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 is the hydrogen nuclear magnetic resonance spectrum of the anion exchange membrane in Experimental Example 1;

[0046] Figure 2 is the water absorption and swelling rate curve of the anion exchange membrane in Experimental Example 1;

[0047] Figure 3 is the mechanical properties of the anion exchange membrane in Experimental Example 2;

[0048] Figure 4 is the ionic conductivity of the anion exchange membrane in Experimental Example 4. DETAILED DESCRIPTION

[0049] The present invention is further described below in conjunction with specific implementation cases.

[0050] The test method involved in the embodiment:

[0051] Ionic conductivity test: The ionic conductivity of AEMs was measured using a CHI660E electrochemical workstation. A 1 cm × 4 cm sample was prepared and soaked in deionized water for 24 hours before testing. Its thickness (T, cm) and width (W, cm) were recorded in the wet film state. Then it was laid flat on the test electrode, and the four-electrode AC impedance mode was used. The temperature range was set to 30°C to 80°C. Each sample was tested three times at each temperature and the average value was taken. The calculation formula for σ is as follows:

[0052]

[0053] Where L represents the distance between the electrode sheets (cm); R represents the impedance of AEMs (Ω).

[0054] Water absorption and swelling rate: 1 cm × 4 cm AEMs samples were immersed in deionized water at 30℃ to 80℃ for 24 h, and the water on the surface of the samples was quickly wiped off to test their quality (W wet ) and length (L wet The sample is then dried to a constant weight and its dry weight (W dry ) and length (L dry ). The calculation formulas of WU and SR are as follows:

[0055]

[0056]

[0057] Mechanical properties test: A material testing machine (Instron-5567A) was used to test the mechanical properties of AEMs. The membrane was cut into 0.6 cm × 3 cm strips, and the effective test size was 0.6 cm × 2 cm. The test was carried out at room temperature at a tensile rate of 1 mm / min. Each sample was tested 5 times and the average value was taken.

[0058] Embodiment 1:

[0059] The first step: preparation of a side chain quinine polymer (in this example, x is 10%, y is 0%, and z is 90%):

[0060] Ar1 selected in this embodiment is p-terphenyl R3 is propane

[0061] 3-Quinuclide and p-terphenyl were added to a three-necked flask with mechanical stirring, the molar ratio of 3-quinuclide and p-terphenyl was 1.5:1, 3-quinuclide was 1.88g in this embodiment, p-terphenyl was 2.30g, and dichloromethane was added to stir and dissolve to make the total concentration of the monomer 2mol / L. Trifluoromethanesulfonic acid was slowly added dropwise under an ice bath environment, wherein the molar ratio of 3-quinuclide to trifluoromethanesulfonic acid was 1:9, and trifluoromethanesulfonic acid was 13.5g in this embodiment. The temperature was raised to 20°C for reaction for 24h, and the reaction was terminated when the reaction liquid became very viscous and climbed the pole. The reaction solution was poured into deionized water and washed to neutrality, and dried at 80°C for 24h to obtain a quinine-based polymer. 2g of quinine polymer was dissolved in dimethyl sulfoxide to make the solution concentration 0.01g / mL, and bromine R3 (1-bromopropane in this embodiment), iodomethane and potassium carbonate were added to the solution respectively, wherein the molar ratio of quinine polymer to 1-bromopropane, iodomethane and potassium carbonate was 1:0.1:1.5:2, and in this embodiment, the quinine polymer was 2g, 1-bromopropane was 0.074g, iodomethane was 0.64g, and potassium carbonate was 0.83g. The above mixture was reacted at 80°C in the dark for 12h. After the reaction was completed, the mixed solution was precipitated in ether, purified, and dried at 80°C for 24h to obtain the target solid, that is, the side chain quinine polymer was obtained.

[0062] Part II: Application of side chain quinine polymers to prepare anion exchange membranes:

[0063] 1 g of the above side chain quinine polymer was dissolved in dimethyl sulfoxide to prepare a 10 wt% solution, filtered and degassed, and the solution was poured onto a clean glass plate and dried at 60°C for 24 h to obtain an anion exchange membrane; the membrane was immersed in a 2M KOH solution for 24 h, and after sufficient ion exchange, it was washed with deionized water until neutral and dried to obtain an OH - Type polymer anion exchange membrane.

[0064] analyze: Figure 1 The side chain quinine polymer in this embodiment was subjected to hydrogen nuclear magnetic resonance spectroscopy ( 1 H-NMR) characterization results. Figure 1There are multiple strong peaks at 7.30-7.80ppm, corresponding to the characteristic peaks of hydrogen on the aromatic ring. There is a broad peak at 4.30ppm, a small peak at 3.52ppm, two broad peaks at 3.21ppm and 3.13ppm, and two broad peaks at 1.95ppm and 1.79ppm, which are the protons at aH, bH, cH and dH of the quinuclidine. The signals of alkyl protons appearing at 0.8-1.7ppm indicate that the side chain grafting is successful.

[0065] Embodiment 2:

[0066] The first step: preparation of a side chain quinine polymer (in this example, x is 50%, y is 25%, and z is 25%):

[0067] Ar1 selected in this embodiment is m-terphenyl R1 is 2,3-butanedione R3 is 1-pentyl fluoride 3-Quininone, m-terphenyl and 2,3-butanedione were added to a three-necked flask with mechanical stirring, and the molar ratio of the three was 0.75:1:0.25, respectively. In this embodiment, 3-quininone was 0.95g, p-terphenyl was 2.30g, and 2,3-butanedione was 0.22g. Dichloromethane was added and stirred to dissolve so that the total concentration of the monomer was 1mol / L. Trifluoromethanesulfonic acid was slowly added dropwise under an ice bath environment, wherein the molar ratio of 3-quininone to trifluoromethanesulfonic acid was 1:4, and trifluoromethanesulfonic acid was 6.0g in this embodiment. The temperature was raised to 30°C for 4h, and the reaction was terminated when the reaction liquid became very viscous and climbed the pole. The reaction solution was poured into deionized water and washed to neutrality, and dried at 80°C for 24h to obtain a quinine-based polymer. 2g of quinine polymer was dissolved in N-methylpyrrolidone to a solution concentration of 0.05g / mL, and bromine R3 (5-bromopentyl fluoride in this embodiment), iodomethane, and potassium carbonate were added to the solution, respectively, wherein the molar ratio of quinine polymer to 1-bromo-5-fluoropentane, iodomethane, and potassium carbonate was 1:0.5:1.5:2, and in this embodiment, the quinine polymer was 2g, 1-bromo-5-fluoropentane was 0.51g, iodomethane was 0.64g, and potassium carbonate was 0.83g. The above mixture was reacted at 20°C in the dark for 48h. After the reaction was completed, the mixed solution was precipitated in ethyl acetate, purified, and dried at 80°C for 24h to obtain the target solid, that is, a side chain quinine polymer was obtained.

[0068] Part II: Application of side chain quinine polymers to prepare anion exchange membranes:

[0069] 1 g of the above side chain quinine polymer was dissolved in N-methylpyrrolidone to prepare a 3 wt % solution, filtered and degassed, and the solution was poured onto a clean glass plate and dried at 80°C for 6 h to obtain an anion exchange membrane; the membrane was immersed in a 1 M KOH solution for 48 h, and after sufficient ion exchange, it was washed with deionized water until neutral and dried to obtain an OH - Type polymer anion exchange membrane.

[0070] analyze: Figure 2 It is the characterization of the water absorption swelling rate of the side chain quinine-based anion exchange membrane in this embodiment. Figure 2 The figure shows the changes in the water absorption and swelling rate of the fully hydrated side-chain quinine anion exchange membrane within 30-80°C. As can be seen from the figure, the water absorption and swelling of the membrane is positively correlated with the temperature, which is in line with the objective law. The water absorption and swelling of the membrane will be greatly affected by the skeleton and side chain. At 30°C, the water absorption and swelling rates are 60.00% and 10.14% respectively, with good dimensional stability.

[0071] Embodiment 3:

[0072] The first step: preparation of a side chain quinine polymer (in this example, x is 30%, y is 17%, and z is 50%):

[0073] Ar1 selected in this embodiment is 9,9-dimethylfluorene R1 is 2,3,4-trifluoroacetophenone R3 is 1-butyl-4-fluorobenzene 3-quininone, trifluoroacetophenone and 9,9-dimethylfluorene were added to a three-necked flask with mechanical stirring, and the molar ratio of the three was 1.25:0.25:1. In this embodiment, 3-quininone was 1.56g, 9,9-dimethylfluorene was 0.49g, and 2,3,4-trifluoroacetophenone was 1.74g. Dichloromethane was added and stirred to dissolve so that the total concentration of the monomer was 1.5mol / L. Trifluoromethanesulfonic acid was slowly added dropwise under an ice bath environment, wherein the molar ratio of 3-quininone to trifluoromethanesulfonic acid was 1:6.5, and trifluoromethanesulfonic acid was 6.0g in this embodiment. The temperature was raised to 25°C for 14h, and the reaction was terminated when the reaction liquid became very viscous and climbed the pole. The reaction solution was poured into deionized water and washed to neutrality, and dried at 80°C for 24h to obtain a quinine-based polymer. 2g of quinine polymer was dissolved in N, N-dimethylformamide to a concentration of 0.03g / mL, and bromo R3 (1-(4-bromobutyl)-4-fluorobenzene in this embodiment), iodomethane and potassium carbonate were added to the solution respectively, wherein the molar ratio of quinine polymer to 1-(4-bromobutyl)-4-fluorobenzene, iodomethane and potassium carbonate was 1:0.3:1.5:2, and in this embodiment, the quinine polymer was 2g, 1-(4-bromobutyl)-4-fluorobenzene was 0.42g, iodomethane was 0.64g, and potassium carbonate was 0.83g. The above mixture was reacted at 50°C in the dark for 30h. After the reaction was completed, the mixed solution was precipitated in ethanol, purified, and dried at 80°C for 24h to obtain the target solid, that is, a side chain quinine polymer.

[0074] Part II: Application of side chain quinine polymers to prepare anion exchange membranes:

[0075] 1 g of the above side chain quinine polymer was dissolved in N, N-dimethylacetamide to obtain a 6 wt% solution, filtered and degassed, and the solution was poured onto a clean glass plate and dried at 70°C for 15 h to obtain an anion exchange membrane; the membrane was immersed in a 1.5 M KOH solution for 36 h, and after sufficient ion exchange, it was washed with deionized water until neutral and dried to obtain OH - Type polymer anion exchange membrane.

[0076] Analysis: The mechanical properties of the prepared side chain quinine-based anion exchange membrane were tested. The test results are as follows: Figure 3 As shown, the tensile strength of the membrane is 30.03MPa and the elongation at break is 15.82%. It can be observed that with the introduction of side chains, the elongation at break increases and the tensile strength decreases. The prepared AEMs have excellent mechanical properties and can meet the application requirements of fuel cells.

[0077] Embodiment 4:

[0078] The first step: preparation of a side chain quinine polymer (in this example, x is 20%, y is 40%, and z is 40%):

[0079] Ar1 selected in this embodiment is biphenyl R1 is pentafluorobenzaldehyde R3 is 1-methylpiperidin octane 3-Quininone, pentafluorobenzaldehyde and biphenyl were added to a three-necked flask with mechanical stirring, and the molar ratio of the three was 0.6:0.4:1. In this embodiment, 3-Quininone was 0.75g, pentafluorobenzaldehyde was 0.78g, and biphenyl was 1.54g. Dichloromethane was added and stirred to dissolve so that the total concentration of the monomer was 1.2mol / L. Trifluoromethanesulfonic acid was slowly added dropwise under an ice bath environment, wherein the molar ratio of 3-Quininone to trifluoromethanesulfonic acid was 1:6, and trifluoromethanesulfonic acid was 9.0g in this embodiment. The temperature was raised to 25°C for 14h, and the reaction was terminated when the reaction liquid became very viscous and climbed the pole. The reaction solution was poured into deionized water and washed to neutrality, and dried at 80°C for 24h to obtain a quinine-based polymer. 2g of quinine polymer was dissolved in N, N-dimethylacetamide to a solution concentration of 0.02g / mL, and bromo R3 (1-(8-bromooctyl)methylpiperidine in this embodiment), iodomethane and potassium carbonate were added to the solution respectively. The molar ratio of quinine polymer to 1-(8-bromooctyl)methylpiperidine, iodomethane and potassium carbonate was 1:0.2:1.5:2. In this embodiment, the quinine polymer was 2g, 1-(8-bromooctyl)methylpiperidine was 0.35g, iodomethane was 0.64g, and potassium carbonate was 0.83g. The above mixture was reacted at 65°C in the dark for 20h. After the reaction was completed, the mixed solution was precipitated in ethyl acetate, purified, and dried at 80°C for 24h to obtain the target solid, that is, a side chain quinine polymer.

[0080] Part II: Application of side chain quinine polymers to prepare anion exchange membranes:

[0081] 1 g of the above side chain quinine polymer was dissolved in N, N-dimethylacetamide to obtain a 4 wt% solution, filtered and degassed, and the solution was poured onto a clean glass plate and dried at 65°C for 20 h to obtain an anion exchange membrane; the membrane was immersed in a 1.56 M KOH solution for 30 h, and after sufficient ion exchange, it was washed with deionized water until neutral and dried to obtain OH - Type polymer anion exchange membrane.

[0082] analyze: Figure 4 It is the ionic conductivity characterization of the side chain quinine anion exchange membrane in this embodiment. As the temperature increases, the ion migration rate of the membrane accelerates, and OH - The conductivity is positively correlated with temperature. Its conductivity at 30°C is 68.0 mS cm -1, 163.2 mS cm at 80 °C -1 . It has excellent ionic conductivity.

[0083] Embodiment 5:

[0084] The first step: preparation of a side chain quinine polymer (in this example, x is 30%, y is 10%, and z is 60%):

[0085] Ar1 selected in this embodiment is diphenylethane R1 is 1-butane isatin R3 is 1-quinine hexane 3-Quininone, N-butane isatin and diphenylethane were added to a three-necked flask with mechanical stirring, and the molar ratio of the three was 0.9:0.1:1, respectively. In this embodiment, 3-Quininone was 1.13g, N-butane isatin was 0.20g, and diphenylethane was 1.82g. Dichloromethane was added and stirred to dissolve so that the total concentration of the monomer was 1.3mol / L. Trifluoromethanesulfonic acid was slowly added dropwise under an ice bath environment, wherein the molar ratio of 3-Quininone to trifluoromethanesulfonic acid was 1:7, and trifluoromethanesulfonic acid was 10.51g in this embodiment. The temperature was raised to 26°C for 10h, and the reaction was terminated when the reaction liquid became very viscous and climbed the pole. The reaction solution was poured into deionized water and washed to neutrality, and dried at 80°C for 24h to obtain a quinine-based polymer. 2g of quinine polymer was dissolved in dimethyl sulfoxide to a concentration of 0.03g / mL, and bromo R3 (6 (bromoalkyl) -1-quinine in this embodiment), iodomethane and potassium carbonate were added to the solution respectively. The molar ratio of quinine polymer to 6 (bromoalkyl) -1-quinine, iodomethane and potassium carbonate was 1: 0.3: 1.5: 2. In this embodiment, the quinine polymer was 2g, 6 (bromoalkyl) -1-quinine was 0.49g, iodomethane was 0.64g, and potassium carbonate was 0.83g. The above mixture was reacted at 60°C in the dark for 20h. After the reaction was completed, the mixed solution was precipitated in methanol, purified, and dried at 80°C for 24h to obtain the target solid, that is, a side chain quinine polymer.

[0086] Part II: Application of side chain quinine polymers to prepare anion exchange membranes:

[0087] 1 g of the above side chain quinine polymer was dissolved in N, N-dimethylacetamide to obtain a 4 wt% solution, filtered and degassed, and the solution was poured onto a clean glass plate and dried at 65°C for 20 h to obtain an anion exchange membrane; the membrane was immersed in a 1.7 M KOH solution for 27 h, and after sufficient ion exchange, it was washed with deionized water until neutral and dried to obtain OH - Type polymer anion exchange membrane.

[0088] Embodiment 6:

[0089] The first step: preparation of a side chain quinine polymer (in this example, x is 25%, y is 17%, and z is 58%):

[0090] Ar1 selected in this embodiment is o-terphenyl and p-quaterphenyl R1 is 2-thiophenecarboxaldehyde R3 is 1-butyl-1-methylpiperidinylbutane- 3-quininone, 2-thiophene carboxaldehyde, o-terphenyl and p-terphenyl were added to a three-necked flask with mechanical stirring, and the molar ratio of the three was 1.25:0.25:0.5:0.5, respectively. In this embodiment, 3-quininone was 1.56g, 2-thiophene carboxaldehyde was 0.28g, o-terphenyl was 1.15g, and p-terphenyl was 1.53g. Dichloromethane was added and stirred to dissolve so that the total concentration of the monomer was 1.1mol / L. Trifluoromethanesulfonic acid was slowly added dropwise under an ice bath environment, wherein the molar ratio of 3-quininone to trifluoromethanesulfonic acid was 1:5, and trifluoromethanesulfonic acid was 7.50g in this embodiment. The temperature was raised to 15°C for 21h, and the reaction was terminated when the reaction liquid became very viscous and climbed the pole. The reaction solution was poured into deionized water and washed to neutrality, and dried at 80°C for 24h to obtain a quinine-based polymer. 2g of quinine polymer was dissolved in dimethyl sulfoxide to a solution concentration of 0.025g / mL, and bromine R3 (1-bromo-5-methylpiperidinylnonane in this embodiment), iodomethane and potassium carbonate were added to the solution respectively. The molar ratio of quinine polymer to 1-bromo-5-methylpiperidinylnonane, iodomethane and potassium carbonate was 1:0.25:1.5:2. In this embodiment, the quinine polymer was 2g, 1-bromo-5-methylpiperidinylnonane was 0.42g, iodomethane was 0.64g, and potassium carbonate was 0.83g. The above mixture was reacted at 75°C in the dark for 13h. After the reaction was completed, the mixed solution was precipitated in methanol, purified, and dried at 80°C for 24h to obtain the target solid, that is, a side chain quinine polymer.

[0091] Part II: Application of side chain quinine polymers to prepare anion exchange membranes:

[0092] 1 g of the above side chain quinine polymer was dissolved in N,N-dimethylformamide to obtain a 5.5 wt% solution, filtered and degassed, and the solution was poured onto a clean glass plate and dried at 65°C for 20 h to obtain an anion exchange membrane; the membrane was immersed in a 1.8 M KOH solution for 27 h, and after sufficient ion exchange, it was washed with deionized water until neutral and dried to obtain an OH - Type polymer anion exchange membrane.

[0093] Embodiment 7:

[0094] The first step: preparation of a side chain quinine polymer (in this example, x is 20%, y is 15%, and z is 65%):

[0095] Ar1 selected in this embodiment is N-ethylcarbazole R1 is 1,3-difluoroacetophenone R3 is valeronitrile and 8-(butyl)-8-methyl-5,8-diazaspiro[4.5]decane 3-Quininone, 1,3-difluoroacetophenone, and N-ethylcarbazole were added to a three-necked flask with mechanical stirring, and the molar ratio of the three was 1.1:0.2:1. In this embodiment, 3-Quininone was 1.38g, 1,3-difluoroacetophenone was 0.31g, and N-ethylcarbazole was 1.95g. Dichloromethane was added and stirred to dissolve so that the total concentration of the monomer was 1.3mol / L. Trifluoromethanesulfonic acid was slowly added dropwise under an ice bath environment, wherein the molar ratio of 3-Quininone to trifluoromethanesulfonic acid was 1:5.5, and trifluoromethanesulfonic acid was 8.25g in this embodiment. The temperature was raised to 16°C for 23h, and the reaction was terminated when the reaction liquid became very viscous and climbed the pole. The reaction solution was poured into deionized water and washed to neutrality, and dried at 80°C for 24h to obtain a quinine-based polymer. 2g of quinine polymer was dissolved in N, N-dimethylacetamide to a concentration of 0.04g / mL, and bromo R3 (1-bromopentane nitrile and 8-(4-bromobutyl)-8-methyl-5,8-diazaspiro[4.5]decane in this embodiment), iodomethane and potassium carbonate were added to the solution respectively, wherein the molar ratio of quinine polymer to 1-bromopentane nitrile, 8-(4-bromobutyl)-8-methyl-5,8-diazaspiro[4.5]decane, iodomethane and potassium carbonate was 1:0.1:0.1:1.5:2, in this embodiment, the quinine polymer was 2g, 1-bromopentane nitrile was 0.097g, 8-(4-bromobutyl)-8-methyl-5,8-diazaspiro[4.5]decane was iodomethane was 0.14g, and potassium carbonate was 0.83g. The above mixture was reacted at 50°C in the dark for 30h. After the reaction was completed, the mixed solution was precipitated in ethanol, purified, and dried at 80° C. for 24 h to obtain the target solid, namely, the side chain quinine polymer.

[0096] Part II: Application of side chain quinine polymers to prepare anion exchange membranes:

[0097] 1 g of the above side chain quinine polymer was dissolved in dimethyl sulfoxide to obtain a 6.5 wt% solution, filtered and degassed, and the solution was poured onto a clean glass plate and dried at 60°C for 20 h to obtain an anion exchange membrane; the membrane was immersed in a 1.5 M KOH solution for 36 h, and after sufficient ion exchange, it was washed with deionized water until neutral and dried to obtain an OH - Type polymer anion exchange membrane.

[0098] Embodiment 8:

[0099] The first step: preparation of a side chain quinine polymer (in this example, x is 30%, y is 21%, and z is 49%):

[0100] Ar1 selected in this embodiment is m-terphenyl and p-terphenyl R1 is 1,3-dibromoacetone R3 is N-hexyl-N-(5-fluoropentyl)-4-methylpiperidine and heptane 3-Quininone, 1,3-dibromoacetone, m-terphenyl and p-terphenyl were added to a three-necked flask with mechanical stirring, and the molar ratio of the four was 1.1:0.3:0.6:0.4, respectively. In this embodiment, 3-Quininone was 1.38g, 1,3-dibromoacetone was 0.64g, m-terphenyl was 1.38g, and p-terphenyl was 0.92g. Dichloromethane was added and stirred to dissolve so that the total concentration of the monomer was 1.3mol / L. Trifluoromethanesulfonic acid was slowly added dropwise under an ice bath environment, wherein the molar ratio of 3-quininone to trifluoromethanesulfonic acid was 1:3, and trifluoromethanesulfonic acid was 4.50g in this embodiment. The temperature was raised to 24°C for reaction for 20h, and the reaction was terminated when the reaction liquid became very viscous and climbed the pole. The reaction solution was poured into deionized water and washed to neutrality, and dried at 80°C for 24h to obtain a quinine-based polymer. 2g of quinine polymer was dissolved in N,N-dimethylformamide to a concentration of 0.07g / mL, and bromo R3 (N-(6-bromohexyl)-N-(5-fluoropentyl)-4-methylpiperidinium bromide and 1-bromoheptane in this embodiment), iodomethane and potassium carbonate were added to the solution respectively, wherein the molar ratio of quinine polymer to N-(6-bromohexyl)-N-(5-fluoropentyl)-4-methylpiperidinium bromide, 1-bromoheptane, iodomethane and potassium carbonate was 1:0.2:0.1:1.5:2, and in this embodiment, the quinine polymer was 2g, N-(6-bromohexyl)-N-(5-fluoropentyl)-4-methylpiperidinium bromide was 0.42g, 1-bromoheptane was 0.11g, iodomethane was 0.14g, and potassium carbonate was 0.83g. The above mixture was reacted at 50°C in the dark for 30h. After the reaction was completed, the mixed solution was precipitated in ethanol, purified, and dried at 80° C. for 24 h to obtain the target solid, namely, the side chain quinine polymer.

[0101] Part II: Application of side chain quinine polymers to prepare anion exchange membranes:

[0102] 1 g of the above side chain quinine polymer was dissolved in dimethyl sulfoxide to obtain a 4.5 wt% solution, filtered and degassed, and the solution was poured onto a clean glass plate and dried at 50°C for 24 h to obtain an anion exchange membrane; the membrane was immersed in a 1.5 M KOH solution for 36 h, and after sufficient ion exchange, it was washed with deionized water until neutral and dried to obtain an OH - Type polymer anion exchange membrane.

[0103] The above-described embodiments merely express the implementation methods of the present invention, but they should not be understood as limiting the scope of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A side chain quininyl polymer, characterized in that: The side chain type quinicinyl polymer comprises a quinuclidine structural unit, an aromatic structural unit Ar1, a functional structural unit R1, and a side chain structure R3. The side chain type quinicinyl polymer has a structure as shown in the following P formula or Q formula: Wherein, x is the molar proportion of the side chain structural unit in the polymer chain, %; y is the molar proportion of the functional structural unit in the polymer chain, %; and z is the molar proportion of the quinuclidine structural unit in the polymer chain, %.

2. A side chain quininyl polymer according to claim 1, characterized in that: In the P formula, x is 10%-50%, z is 50%-90%; in the Q formula, x is 10%-50%, y is 0%-40%, and z is 25%-90%.

3. A side chain quininyl polymer according to claim 1, characterized in that: The R1 structure is at least one of the following, Wherein, R2 in the R1 structure is hydrogen or a C1-C10 alkyl group; The Ar1 structure is at least one of the following aromatic structural monomers: Wherein, R2 in the Ar1 structure is hydrogen or C1-C 10 The alkyl group; The R3 comprises at least one of the following structures: Wherein, R2 in the R3 structure is hydrogen or a C1-C10 alkyl group.

4. A method for preparing a side chain quininyl polymer according to any one of claims 1 to 3, characterized in that: The following steps are involved: The first step is to synthesize quinine-based polymers; Dissolve Ar1 in an organic solvent, add 3-quininone or a mixture of 3-quininone and R1 after dissolution, drop trifluoromethanesulfonic acid, stir and react at a certain temperature, end the reaction when the reaction liquid becomes very viscous and climbs the pole, pour the reaction liquid into deionized water for precipitation, wash, filter and dry to obtain a quininyl polymer; The second step is to prepare a side chain quinine-based polymer; The quinine-based polymer prepared in the first step is dissolved in solvent X, and then potassium carbonate, bromide R3 and iodomethane are added to the mixture, and the mixture is reacted for a period of time in the dark at a certain temperature; after the reaction, the mixed solution is precipitated in precipitant A, purified and dried to obtain a side chain quinine-based polymer.

5. The method for preparing a side chain quininyl polymer according to claim 4, characterized in that: In the first step: the reaction temperature is 20-30°C, and the reaction time is 4-24h; The molar concentration of Ar1 in the organic solvent is 1.0-2.0 mol / L; When 3-quininone is added to Ar1, the molar ratio of Ar1 to 3-quininone is 1:(1-1.5), and the molar ratio of 3-quininone to trifluoromethanesulfonic acid is 1:4-9; when Ar1 is added to a mixture of 3-quininone and R1, the molar ratio of Ar1, 3-quininone and R1 is 1:(1-1.5):(0.01-0.5), and the molar ratio of 3-quininone to trifluoromethanesulfonic acid is 1:4-9.

6. The method for preparing a side chain quininyl polymer according to claim 4, characterized in that: In the second step: the reaction temperature is 20-80°C, and the reaction time is 12-48h; The molar ratio of the quinine polymer: bromide R3: iodomethane: potassium carbonate is 1: (0.1-0.5): 1.5: 2; The mass concentration of the quinine-based polymer in the solvent X is 0.01-0.05 g / mL.

7. The method for preparing a side chain quininyl polymer according to claim 4, characterized in that: The drying temperature in the first step is 80°C and the drying time is 24h; the drying temperature in the second step is 80°C and the reaction time is 24h; The organic solvent in the first step is dichloromethane; the solvent X in the second step is one or a mixture of two or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; In the second step, the precipitant A is one or a mixture of two or more of ether, methanol, ethanol, ethyl acetate, acetone and water.

8. An application of the side chain quininyl polymer according to any one of claims 1 to 3, characterized in that: The side chain quinine polymer is used to prepare a side chain quinine polymer anion exchange membrane. - The anion exchange membrane has the structure shown in the following formula S, T:

9. The use of a side chain quininyl polymer according to claim 8, characterized in that: The method for preparing a side chain quininyl polymer anion exchange membrane from a side chain quininyl polymer is specifically as follows: a dried side chain quininyl polymer is dissolved in a solvent Y to prepare a membrane liquid, followed by filtering, degassing, casting, immersing in an alkali solution, washing with water until neutral, and drying to obtain a side chain quininyl polymer anion exchange membrane.

10. The use of a side chain quininyl polymer according to claim 9, characterized in that: The membrane solution concentration is 3-10wt%; The drying temperature is 60-80°C and the time is 6-24 hours; The soaking time is 24 to 48 hours, and the alkali solution is 1 to 2 mol / L KOH solution; The solvent Y is one or a mixture of two or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

Citation Information

Patent Citations

  • Polyaryl quinine polymer, preparation method and anion exchange membrane prepared from polyaryl quinine polymer

    CN117106161A

  • Anion exchange membrane based on high free volume main chain and preparation method thereof

    CN117986651A

  • Fluorine-formaldehyde-group-containing piperidine anion exchange membrane and preparation method thereof

    CN118344634A

  • Cationic polymer based on halogenated m-terphenyl group as well as preparation method and application of cationic polymer

    CN118580470A

  • Fluorine-containing piperidine anion exchange membrane and preparation method thereof

    CN118620151A